Where are the vulnerable children? Identification and comparison of clusters of young children with health and developmental vulnerabilities across Queensland. - Wala Draidi Areed; Aiden Price; Kathryn Arnett; Kerrie Mengersen; Helen Thompson (PLoS ONE, 2024)
This study aimed to better understand the vulnerability of children in their first year of school, aged between 5 years 5 months and 6 years 6 months, based on five health and development domains. Identification of subgroups of children within these domains can lead to more targeted policies to reduce these vulnerabilities. The focus of this study was to determine clusters of geographical regions with high and low proportions of vulnerable children in Queensland, Australia. This was achieved by carrying out a K-means analysis on data from the Australian Early Development Census and the Australian Bureau of Statistics. The clusters were then compared with respect to their geographic locations and risk factor profiles. The results are made publicly available via an interactive dashboard application developed in R Shiny.